(untitled) (Journal of Engineering and Health Sciences, 2019)
Shape recognition is an important aspect in Computer Vision. From the point of view of different object recognition problem has been solved and some of the modifications in the method of recognition is still ongoing. This is the main reason that the identification form used in applications with a large number of major challenges, including sound, degradations. In this paper a number of forms of identification methods have been defined from which researchers can get an idea for an efficient technique modified.